Sexual Education Using e-Booklet for Mosque Youth Community - Sari, Nona Kumala (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2024)
The lack of sexual education in adolescents has an impact on the low ability of adolescents to protect themselves from promiscuity and the risk of sexually transmitted diseases. In this regard, this community service aims to analyse the social problems of adolescents, the application of sexual education to adolescents using e-booklets, and the impact of the application of education. This activity was carried out in the adolescent community in Pantai Labu Pekan Village, using participatory action research (PAR) methodology. The programme strategy consists of three steps, namely problem analysis, goal analysis and programme strategy analysis. The results of community service activities revealed that the initial level of understanding of adolescents before the service was carried out was still very minimal, it was evident that out of 23 adolescents, 3 participants were in the sufficient understanding category, 16 people in the poor category, and 4 people in the poor category. To increase understanding, a sexual education seminar using e-booklets was conducted, focusing on three materials, namely Islamic values, psychology, and reproductive health. The level of understanding after the service has increased, namely out of 23 participants, 11 participants are in the excellent category, 10 participants in the good category, and 2 participants in the fair category, and there are no more participants who are in the poor and unfavourable categories.